Cellular Response of Surface Functionalized polymeric fiber mesh coating onto dental titanium Implants = Respuesta celular de la superficie funcionalizada de un recubrimiento nanofibrilar polimérico en implantes dentales de titanio - Vázquez Vázquez, Febe Carolina
The purpose of this in vitro study was to develop a polymeric nanofiber mesh coating for titanium implant surfaces and assess its contribution to the cellular response. Two types of dental implants TiUltraTM and TiUniteTM (Nobel Biocare) were coated with poly (lactic acid) nanofibers fabricated using the air-jet spinning technique (AJS). The morphology of the polymeric nanofibers was characterized by scanning electron micros copy (SEM), and the biocompatibility was evaluated in terms of cell adhesion by using human fetal osteoblasts (hFOB). The cellular localization was observed under a fluorescent microscope, and the gene expression of Col 1, ALP, and OCN was evaluated by RT-PCR. The micrographs showed that the polymeric nanofiber coated the titaium (Ti) dental implant surfaces with a randomized deposition anchored between the depth of the threads, and well-interconnected pores were observed. Cell adhesion increased significantly (P<.05) more on the surfaces of Ti dental implants coated with the polymeric nanofiber mesh than on those not coated. After 21 days, the cell adhesion decreased significatively on the uncoated surfaces (P<.05). Col 1 and ALP genes showed a higher level of expression on dental implant surfaces coated with polymeric nanofibers mesh than on uncoated surfaces. Coating Ti dental implant surfaces with polymeric nanofiber mesh is a straightforward deposition technique for stimulating the cell response and improving the gene expression of osteogenic markers.